The far-lateral craniotomy: tips and tricks - Feres Chaddad Neto; Hugo Leonardo Doria-Netto; José Maria de Campos Filho; Mateus Reghin Neto; Albert L Rothon Jr; Evandro de Oliveira (Arquivos de Neuro-Psiquiatria)
This article intends to describe in a didactical and practical manner the suboccipital far-lateral craniotomy. This is then basically a descriptive text, divided according to the main stages involved in this procedure, and that describes with details how the authors currently perform this craniotomy.